Adsorption of volatile organic compounds onto activated carbon cloths derived from a novel regenerated cellulosic precursor - Ramos, María Eva (2010)
Activated carbon cloths (ACC) were prepared from lyocell, a novel regenerated cellulose nanofibre fabric, by phosphoric acid activation in inert atmosphere at two different final thermal treatment temperatures (864 and 963 °C). Benzene, toluene and n-hexane isotherms at 298 and 273 K were measured in order to gain insight into the porous structure of the ACC and to evaluate their performance for the removal of volatile organic compounds (VOCs). The Dubinin–Radushkevich equation was employed to evaluate textural parameters of the ACC. The textural characteristics of the ACC were compared with those previously determined from nitrogen (77 K) and carbon dioxide (273 K) adsorption data. The samples were essentially microporous. The textural parameters calculated from the hydrocarbon isotherms were in good agreement with those evaluated from nitrogen isotherms for the ACC with the wider microporosity. Additionally, the Freundlich model provided a good description of the experimental isotherms for the three volatile organic compounds. The ACC obtained at the higher temperature exhibited a larger adsorption capacity. The ACC were also electrically conductive and showed potential for regeneration by the Joule effect, as determined from macroscopic electrical measurements before and after n-hexane adsorption.